Assessing Oral Cancer Awareness Among Dental Students - NAMDAR PEKİNER, FİLİZ MEDİHA; KESER, GAYE (SPRINGER, 2019)
The aim of this study was to assess oral cancer awareness among undergraduate dental students in Marmara University Faculty of Dentistry. A validated questionnaire which tested oral cancer awareness was given to third- and fifth-year students of the dental faculty of Marmara University. A total of 198 students participated in this survey. Knowledge of oral cancer risk factors and diagnosis procedures, dentistry student's attitude towards oral cancers, management practice regarding oral cancer, and oral cancer information sources were assessed using 25 questions. The data were analyzed with IBM SPSS Statistics 22.0 program. Among 198 participant dentistry students, there were 99 (50%) third-grade and 99 (50%) fifth-grade students. The largest number of the third- and last-grade students identified tobacco (98%) and alcohol usage (87.4%), prior oral cancer lesions (94.9%), viral infections (91.9%), UV exposure (94.4%), betel quid chewing (84.8%), older age (62.1%), and low consumption of fruit and vegetables (85.4%). Both groups showed higher scores in indicating squamous cell carcinoma as the most common form of oral cancer (p<0.05); yet, third-grade students performed significantly higher scores in indicating erythroplakia and leukoplakia for most likely to be precancerous (p=0.001; p<0.05). This study highlighted the importance of improved educational methods for dentistry on oral cancer detection and prevention.
Keywords: Oral cancer; Awareness; Dentistry students; EARLY-DIAGNOSIS; KNOWLEDGE; DELAY; HEAD; OPINIONS; CAVITY; RISK